2016
DOI: 10.1093/rheumatology/kew035
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide association study identifiesSLC8A3as a susceptibility locus for ACPA-positive rheumatoid arthritis

Abstract: SLC8A3 was identified as a new risk locus for ACPA-positive RA. This study demonstrates the advantage of analysing relevant subsets of RA patients to identify new genetic risk variants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 18 publications
2
16
0
Order By: Relevance
“…Association of BLK SNVs to RA was initially documented in North American and Korean patients (Gregersen et al, 2009;Freudenberg et al, 2011), and later in British, Colombian, and Han Chinese patients (Deshmukh et al, 2011;Orozco et al, 2011;Viatte et al, 2012;Huang et al, 2017). Nevertheless, other GWA or candidate gene studies carried out in some Arab countries and Europeans from the Netherlands and Spain, and even another Chinese group failed to replicate this finding (Suarez-Gestal et al, 2009;Génin et al, 2013;Jiang et al, 2014;Bossini-Castillo et al, 2015;Julià et al, 2016;Zhu et al, 2016;Saxena et al, 2017). As far as we know, the only study conducted in Latin-Americans thus far, found an association of both BLK rs13277113A/G and rs2736340T/C SNVs and risk for RA in Colombians (Deshmukh et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Association of BLK SNVs to RA was initially documented in North American and Korean patients (Gregersen et al, 2009;Freudenberg et al, 2011), and later in British, Colombian, and Han Chinese patients (Deshmukh et al, 2011;Orozco et al, 2011;Viatte et al, 2012;Huang et al, 2017). Nevertheless, other GWA or candidate gene studies carried out in some Arab countries and Europeans from the Netherlands and Spain, and even another Chinese group failed to replicate this finding (Suarez-Gestal et al, 2009;Génin et al, 2013;Jiang et al, 2014;Bossini-Castillo et al, 2015;Julià et al, 2016;Zhu et al, 2016;Saxena et al, 2017). As far as we know, the only study conducted in Latin-Americans thus far, found an association of both BLK rs13277113A/G and rs2736340T/C SNVs and risk for RA in Colombians (Deshmukh et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In 2009 and 2011, two genome wide association studies (GWAS) carried out in European and Asian derivedpopulations, respectively, identified some single nucleotide variants (SNVs) in the BLK gene to be associated with risk for rheumatoid arthritis (RA) (Gregersen et al, 2009;Freudenberg et al, 2011). However, other GWA or candidate gene studies have failed to replicate these findings (Génin et al, 2013;Jiang et al, 2014;Orozco et al, 2014;Bossini-Castillo et al, 2015;Zhu et al, 2016;Julià et al, 2016;Saxena et al, 2017), except in patients from United Kingdom, Colombia, and China (Deshmukh et al, 2011;Orozco et al, 2011;Viatte et al, 2012;Huang et al, 2017). On the other hand, the BANK1 gene, which was identified as an important risk factor for systemic lupus erythematosus (SLE) (Kozyrev et al, 2008), does not appear to be associated with RA through GWA (Gregersen et al, 2009;Freudenberg et al, 2011;Jiang et al, 2014;Orozco et al, 2014;Bossini-Castillo et al, 2015;Julià et al, 2016;Saxena et al, 2017) or candidate gene studies (Suarez-Gestal et al, 2009;Orozco et al, 2011;Génin et al, 2013;Huang et al, 2017), except for the BANK1 rs3733197G/A (Ala383Thr; non-synonymous polymorphism) SNV, which showed an association with RA in Spanish and Argentine patients (Orozco et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach culminated in 2014 with the publication of a transethnic mega-meta-analysis of all available GWAS datasets worldwide, comprising data from over 100,000 subjects of European and Asian ancestries (29,880 RA cases and 73,758 controls) for around 10 million SNPs [41]. Since then, further RA susceptibility risk loci have been identified (e.g., BACH2 [52], 22q12 [53], CDK5RAP2, and DPP4 [54], SLC8A3 [55]), bringing the total number of associations outside the HLA to 106 (Fig. 1).…”
Section: Susceptibilitymentioning
confidence: 99%
“…Various genetic biomarkers were detected through genome-wide association studies (Massey et al, 2018;Shadrina et al, 2018;Lopez-Mejias et al, 2019). Multiple genetic mutations were detected to be statistically associated with the susceptibility for RA, including the SNPs in the genes interferon regulatory factor 4 (IRF-4) (Lopez-Isac et al, 2016) and Solute Carrier family 8 (SLC8A3) (Julia et al, 2016). Genetic factors were also observed to be associated with the treatment responses of the tumor necrosis factor alpha inhibitors (TNFi) (Massey et al, 2018) and the methotrexate (MTX) monotherapy (Taylor et al, 2018).…”
Section: Introductionmentioning
confidence: 99%